Untapping The Potential of Parental Engagement in Early Learning in Zanzibar - Shehe Abdalla Muhammed; Msellem Mohamed Ali; Tamasha Juma Therea (Indonesian Educational Research Journal, 2025)
Children's academic success has been consistently linked to the involvement of parents in pre-primary education. Specifically, the objectives were: to identify forms of parental involvement; explore reasons for parents’ involvement; examine challenges affecting effective involvement, and suggest strategies for improvement. This study assessed the nature of parental involvement in Zanzibar's pre-primary education based on Joyce Epstein’s six types of parental involvement framework. The study utilized a mixed-methods design, involving 90 parents from ten pre-primary schools in South district Zanzibar.  Quantitative data was collected through a questionnaire from 90 parents while face-to-face interviews were done with 12 pre-primary teachers. Quantitative data were subjected to descriptive statistics, and qualitative data were analyzed thematically. The mean scores and standard deviations (SD) from qualitative data across involvement categories revealed strengths in parenting, communication, and home-learning activities involvement while volunteering and decision-making recorded lower levels. Parents’ reasons for their involvement include developing child’s progress and better learning, doing their responsibilities, following up for the child’s encouragement, and building relationships with the school. Challenges for ineffective involvement include time constraints, limited teacher support, and lack of awareness. Recommendations emphasize fostering awareness, improving parent-school relationships, and encouraging active participation.